Facile Biopolymer Assisted Synthesis of Hollow SnO2 Nanostructures and Their Application in Dye Removal. Issue 15 (26th September 2016) - Chowdhury, Rakesh; Barah, Nilotpal; Rashid, Md. Harunar
Abstract: Herein, we report the synthesis of SnO2 nanostructures by alkaline hydrolysis of the corresponding metal ions in presence of biopolymer additive such as carboxy methylcellulose at 65 °C. X‐ray diffraction studies confirmed the formation of pure crystalline tetragonal SnO2 nanostructures. Microscopic results revealed that addition of biopolymer results in the formation of hollow nanostructures. The sizes of such hollow nanostructures are controllable by varying the concentration of the biopolymer. The hollow nanostructures are further characterized by other spectroscopic techniques such as UV‐vis spectroscopy, photoluminescence spectroscopy, X‐ray photoelectron spectroscopy and energy dispersive X‐ray spectroscopy. These hollow SnO2 nanostructures are porous and show excellent adsorption capability in removal of organic dye, methylene blue from its aqueous solution at room temperature. The recovered SnO2 nanostructures can be reused in successive batches for dye adsorption without much losing its adsorption capacities. Abstract : Hollow SnO2 nanostructures as dye adsorbent: Hollow SnO2 nanostructures were synthesized by alkaline hydrolysis using biopolymer as additive. These hollow SnO2 nanostructures show excellent dye adsorption performance.